Reseña de: Tsuchiya, Akiko; Acree Jr., William G. (coords): Empire’s End: Transnational Connections in the Hispanic World, Nashville (Tennessee), Vanderbilt University Press, 2016, 221 p. - Copeland, Eva María (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2017)
Reseña de: Tsuchiya, Akiko; Acree Jr., William G. (coords): Empire’s End: Transnational Connections in the Hispanic World, Nashville (Tennessee), Vanderbilt University Press, 2016, 221 p.